Upaya Kepala Madrasah Dalam Menumbuhkan Minat Peserta Didik Untuk Memilih Jurusan Agama(Studi Kasus di Madrasah Aliyah Negeri Sukoharjo Kelas X Tahun Ajaran 2016/2017) - Mustaqim, Nurul; , Dr. Syamsul Hidayat, M.Ag (2017)
The head of a madrasah in educational units is a leader. As a leader, the head of the madrasah is responsible for the achievement of educational goals. Department of religion is one of the majors that must be held in Madrasah Aliyah Negeri. Lack of students' understanding of religious majors makes the interest of learners to choose the department of religion is very minimal. From the above problems the formulation of the problem is how the efforts of madrasah head to cultivate the interest of learners to choose the religious department. The purpose of this study is to find out what efforts are made by the head of madrasah to foster the interest of students to choose a religious department. This research uses descriptive qualitative approach method. This research was conducted at MAN Sukoharjo from March to May 2017. The subjects in this study were the head of MAN Sukoharjo and the students of the X class of academic year 2016/2017. Data were collected by observation, interview and documentation. To check the validity of data using triangulation technique while data analysis using interactive analysis techniques, the steps taken are data collection, data reduction, data presentation, and conclusion. Based on the research, the results obtained are the efforts made by the head of madrasah in growing the interest of students to choose the religious majors are as follows: 1) Provide stimulation by providing motivation to learners during the flag ceremony and when in the classroom. 2) Cooperate with teachers especially BK teachers and religious teachers in an effort to cultivate new interests in learners on the sidelines of learning. 3) Disseminating / giving information to the guardians by holding meetings with the guardian and giving a letter about the religious department. 4) The policy of madrasah head to open extracurricular activities Read Write Al-Qur'an (BTA) for all students.